(untitled) (MAUSAM, 1970)
Heat flows into soils were evaluated in the open and in a sugarcane field by using the temperature-gradient method. The measurements were made at the Sugarcane Research Station, on four representative days in November and December 1967, and January and February 1968. The magnitude and the diurnal range of heat-flux in the sugarcane field were considerably smaller than those ill the open. The times of occurrence of maximum heat flux were almost the same (about 1200 hrs) In both the open and the sugarcane field. Minimum values of heat-flux, however, occurred in the late evening in the open and a-t early morning in the cane field, the lag varying from 6 to 10 hours.